Legacy and emerging contaminants in common guillemot Uria aalge eggs in Ireland and Wales. (November 2021) - Power, Andrew; White, Philip; McHugh, Brendan; McGovern, Evin; Murphy, Sinéad; Berrow, Simon; Schlingermann, Moira; Gately, Cillian; Tannian, Marissa; Newton, Stephen; Crowley, Denis; O'Hea, Linda; et al.
Abstract: Guillemot eggs from multiple Irish colonies and one Welsh colony were analysed for legacy pollutants such as polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and other organochlorine compounds (OCs), as well as metals. Stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) were measured in eggs to understand the influence of diet on contaminant levels detected. Wide-scope target and suspect screening techniques were used on a single guillemot egg, providing novel information on contaminants of emerging concern. Stable isotope ratio analysis showed that guillemots from Great Saltee Island and Lambay Island (Ireland's east coast) had a similar carbon source (δ 13 C) and fed at similar trophic levels (δ 15 N), pollutant levels were higher in eggs from Lambay Island near Dublin, Ireland's industrialised capital city. Guillemot eggs from Aughris Head (Atlantic west coast of Ireland), and Skomer Island (Wales) had differing isotopic niches to other colonies. Egg samples from Aughris Head had the lowest levels of pollutants in this study (with the exception of mercury) and amongst the lowest levels reported worldwide. In contrast, Skomer Island had the highest level of pollutants with higher concentrations of Σ 16PCB, Σ 6PBDE and HCB than Irish colonies, most likely a result of its proximity to historically industrial areas. Levels of PCBs, p, p' –DDE and mercury in guillemot eggs have decreased over time according to this study, in concurrence with worldwide trends. Levels of pollutants in guillemot eggs, in this study, fall below existing thresholds for adverse effects in other species, with the exception of mercury. Highlights: Guillemot eggs from 3 Irish sites and 1 from Wales analysed for legacy pollutants. Pollutants highest in Skomer (Wales), lowest in Aughris (Ireland, Atlantic Ocean). Stable isotope ratio analysis showed dietary differences between sites. Novel screening techniques used for contaminants of emerging concern. Levels of pollutants below thresholds for adverse effects, except mercury.